Health literacy: a strategy for success in patient-physician communication - Mohsen Shamsi; Raheleh Soltani; Hadi Mohammadi (Payesh, 2024)
Dear Editor, Communicating correctly and effectively with clients is considered one of the most important and essential skills for health professionals. However, they mainly use jargon in the process of communicating with clients, and sometimes there is a lot of information that is beyond the ability of their clients. Thus, paying attention to health literacy as one of the most important strategies to improve the quality of patient-physician communication in both providers and recipients of health services. However, the main and major focus of health literacy research has been patients, and the other side of the problem, that is, health professionals and their communication skills, has received less attention; While the lack of familiarity with the concept of health literacy and lack of attention to its principles by health professionals during every encounter with clients and in general, the process of communicating with clients, can be challenging and ultimately might lead to a communication failure.